Physical exercise and diabetes during childhood - Giannini, Cosimo; Mohn, A.; Chiarelli, Francesco (Acta Biomedica Atenei Parmensis, 2006)
Active life and physical fitness may represent the most effective strategies to prevent chronic diseases and to improve growth and development for children, including those with diabetes. Observational studies have demonstrated the association between life style and prevention of chronic diseases in the general population. These studies have been showed a reduction of morbidity for vascular diseases in trained subjects who present adequate cardiovascular fitness and practise regular exercise. The exercise-related protective effects may be mediated in part through components of the metabolic syndrome: improved insulin sensitivity, decreased weight and visceral fat accumulation, reduced low density lipoprotein (LDL) and triglycerides, increased high density lipoprotein (HDL), decreased blood pressure. These effects are more significant in patients with type 1 diabetes (T1DM), because hyperglycemia-related morbidity and mortality are associated with chronic complications. In particular, improved insulin sensitivity may determine a better glucose profile which in turn may positively influence the diabetes-related microvascular complications. Furthermore, improved blood pressure and normalization of lipid profile may also contribute to the prevention of vascular complications. Nonetheless, physical activity can improve psychological well-being by increasing self-esteem and enhancing quality of life. Although patients withT1DM may participate in all kind of sports and physical activities, there are several potential adverse events, including hypoglycemic and hyperglycemic episodes, that can occur. Thus, patients and health professionals have to know in details the physiological effect of physical exercise and its metabolic events in order sport to be healthy and enjoyable for all children, adolescents and young adults with T1DM.